2002
DOI: 10.1021/ja0272989
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrochemical Single-Walled Carbon Nanotubes

Abstract: Metalloproteins and enzymes can be immobilized on SWNTs of different surface chemistry. The combination of high surface area, robust immobilization and inherent nanotube electrochemical properties is of promising application in bioelectrochemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
270
0
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 435 publications
(288 citation statements)
references
References 12 publications
10
270
0
7
Order By: Relevance
“…glucose oxidase [9]. Azamian et al [10] observed adsorption of ferritin protein onto SWNTs which resulted in the solubilisation of SWNTs in water. In contrast, Dai and co-workers reported that incubating SWNTs grown on a TEM grid in aqueous ferritin solution resulted in no observable adsorption [11].…”
Section: Introductionmentioning
confidence: 99%
“…glucose oxidase [9]. Azamian et al [10] observed adsorption of ferritin protein onto SWNTs which resulted in the solubilisation of SWNTs in water. In contrast, Dai and co-workers reported that incubating SWNTs grown on a TEM grid in aqueous ferritin solution resulted in no observable adsorption [11].…”
Section: Introductionmentioning
confidence: 99%
“…The functionalization of CNTs with biomolecules can be realized by both noncovalent-and covalent-based modification, and several biomolecules can also become adsorbed directly to CNTs noncovalently. In particular, antibodies (60), enzymes (61), and peptides (62) can bind nonspecifically to the exterior surface of CNTs, whereas oligonucleotides can bind to the surface as well as the open cavity space of CNTs. DNA-CNT interactions in water are suggested to result from DNA base-stacking at the CNT surface, with the hydrophilic sugarphosphate backbone oriented outward toward the aqueous medium (63).…”
Section: Notesmentioning
confidence: 99%
“…25,26 In the meantime, GNP materials were immobilized in combination with CNT on the amine-terminated PTH film through the strong interaction of Au to -NH2.…”
Section: Design Of the Enzyme Electrode With The Pth-cnt-gnp Platformmentioning
confidence: 99%